(untitled) (AYUSHDHARA, 2018)
Aging is defined as process of growing old, damage to cells, tissues and organs with the passage of time. Ayurveda being ancient system of medicine, clearly described about Jara and defined it as “Vayakrita slathamamsadi avastha” with other Lakshanas like Khalitya, Palitya, Smritinasha, Ksheenabala etc. In the blown up human civilization of present era and in the midst of increased various stress, improper diet, lack of exercise, low quality of food grain etc has adversely affected on the process of aging and may cause signs of premature aging, which is definitely an alarming sign and it may indicate the shorten lifespan. In Ayurveda prevention of disease has given utmost importance. To prevent any of the diseases one must know the causative factors properly, where Nidanaparivarjana is considered as first line of treatment in most of the diseases. “Everyone grows old”, Jara is an inescapable part of life but premature aging is an unnatural, untimely process. Prevention of this Akaalaja jara is possible only by understanding its Nidanas. There are so many internal and external factors which contribute for premature aging and this article is intended to explore those factors like Aharaja, Viharaja, Manasika nidanas to aim for targeted treatment.